How to improve business performance in global competition? (Case Study On Batik Komar Bandung) - Febrianti, R. Adjeng Mariana; Nugroho, Wahyu; Wijanarko, Sigit; Saudi, Mohd Haizam (CENTRAL ASIA AND THE CAUCASUS, 2022)
The development of the batik industry in Indonesia is increasing, especially when there are digital business platforms. Many of the business people to integrate their marketing through social media so that demands for the organization to reformulate its strategy. This study aims to examine and analyze the factors that can affect the strategy of improving organizational performance. In this case, the variables studied are entrepreneurial competence, market orientation, and innovation strategy on business performance in contemporary batik (Komar). The population in this study were consumers as many as 400 people then the sample was selected as many as 200 people. This type of research is quantitative using explanatory methods with valid and reliable data collection instruments with questionnaires. In terms of data analysis techniques, researchers used multiple linear regression. This study finds that entrepreneurial competence, market orientation, and innovation strategy partially and simultaneously have a positive and significant effect on business performance in contemporary batik organizations (komar). However, in this study, found limitations, namely that in the question of place facilities, so the researchers recommend to organizations to improve facilities to provide comfort for consumers.